Assisted E-Book Media Development Hyzine-Flipbook Food Chain Materials Science Subjects to Increase Students' Interest in Learning in Elementary School - Sari, Ainiyyah Yunita; Zulherman, Zulherman (Journal of Educational Sciences, 2025)
Modern elementary education struggles with engaging science instruction, particularly for abstract concepts like food chains requiring complex visualization. Traditional media fails to capture student attention, necessitating innovative digital solutions aligned with contemporary learning preferences. This study develops and evaluates Hyzine-Flipbook assisted e-book media effectiveness for teaching food chain concepts to fifth-grade students, measuring impact on learning outcomes and academic interest levels. Research and Development methodology with ADDIE framework was implemented across three elementary schools. Data collection involved pre-test/post-test assessments, questionnaire surveys, and expert validation from material, media, and language specialists. Statistical analysis included normality tests, homogeneity analysis, N-Gain calculations, and independent t-tests. Results: Experimental groups showed superior performance with N-Gain scores of 73-81 versus control groups' 19-20. Statistical analysis revealed highly significant differences (p < 0.001) with mean improvements exceeding 30 points. Student responses indicated "Very Feasible" qualifications (81-93%) for experimental groups, while expert validation achieved 88% (material), 80% (media), and 84% (language) scores. Hyzine-Flipbook assisted e-book media significantly enhances food chain comprehension and stimulates learning interest through interactive multimedia integration, representing a scalable solution for transforming elementary science education digitally.